Telemetric capsule-based upper gastrointestinal tract – blood detection – first multicentric experience. Issue 5 (1st June 2022) - Brunk, Thomas; Schmidt, Arthur; Hochberger, Juergen; Wedi, Edris; Meier, Benjamin; Braun, Georg; Neser, Frank; Schneider, Maximilian; Kandler, Jennis; Bauerfeind, Peter; Repp, Michael; Weingart, Vincens; et al.
Abstract: Introduction: Risk stratification in upper gastrointestinal bleeding (UGIB) currently relies on clinical parameters and risk scores. HemoPill ® acute (Ovesco Endoscopy, Tuebingen, Germany) is a pill-shaped, orally administered sensor capsule for real-time blood detection. The aim of this study was to evaluate the system in clinical routine. Material and methods: Sixty-one consecutive patients in whom the HemoPill ® had been used at 12 international hospitals between July 2019 and March 2020 were retrospectively analysed. Indications for application were the clinical suspicion of UGIB, small bowel bleeding, of rebleeding after hemostasis. Primary endpoints were technical success and bleeding detection/exclusion. Secondary endpoints included adverse events and change of clinical course. Results: The capsule was used in 45 (73%) patients with UGIB, in 12 (20%) patients with small bowel bleeding and in four (7%) patients for exclusion of rebleeding. Technical success was 98%. 35/60 (58%) cases were capsule-positive and among these, endoscopy showed bleeding in 20/35 (57%) cases. None of the 25 capsule-negative patients rebled. Emergency endoscopy could be avoided in 18/25 (72%) cases. Serious adverse events did not occur. Conclusion: HemoPill ® -based blood detection is feasible and safe. Negative capsule results might 'downgrade' the need for urgent endoscopy.